Tanggung Jawab Notaris terhadap Akta Perjanjian Pengikatan Jual Beli yang Tidak Sesuai dengan Harga Sebenarnya - Hutama, Kristian; Priyono, Ery Agus (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Buying and selling land is the transfer of land rights from one person to another. This is often done because land has economic value. In a sale and purchase agreement, the object and price must be stated clearly. This is related to income tax (PPH) and exemption of rights. Ata Land and Building (BPHTB) this tax will arise with the transfer of land rights. This makes some people do not mention the actual price in the agreement to avoid the amount of tax that must be paid. This writing aims to know and describe the responsibilities of a notary in making a sale and purchase agreement. The writing method takes normative juridical, namely emphasizing the problems that are researched based on reality through related literacies. The notary is only tasked with making the contents of the agreement based on the agreement of the parties. In addition, the notary has tried to take preventive measures such as writing in detail, in detail and as completely as possible and for the legal consequences of the agreement it will not meet the objective requirements, namely a certain matter and a lawful cause because the price in the Sale and Purchase Agreement (PPJB) does not match at the actual price so that the deed is automatically null and void.